2006
DOI: 10.3928/1081-597x-20060401-08
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront-guided Enhancements Using the WaveLight Excimer Laser in Symptomatic Eyes Previously Treated With LASIK

Abstract: PURPOSE:To describe our clinical experience in wavefront-guided LASIK enhancements using the WaveLight ALLEGRETTO system (WaveLight Technologie AG, Erlangen, Germany) for symptomatic eyes previously treated with standard LASIK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Although we are unable to identify a significant number of patients for a 6-month follow-up, a previous 8-month small-series study that included wavefront-guided hyperopia retreatments after conventional LASIK found good stability from 3 to 8 months as well as a reduction in HOAs. 16 Prospective randomized studies comparing wavefront-guided LASIK and conventional LASIK are needed to reach a clinically valid conclusion to the question of whether newer wavefront-guided technology is comparatively better for correcting HOAs than conventional LASIK in patients with recurrent treatment for hyperopia and hyperopic astigmatism.…”
Section: Discussionmentioning
confidence: 98%
“…Although we are unable to identify a significant number of patients for a 6-month follow-up, a previous 8-month small-series study that included wavefront-guided hyperopia retreatments after conventional LASIK found good stability from 3 to 8 months as well as a reduction in HOAs. 16 Prospective randomized studies comparing wavefront-guided LASIK and conventional LASIK are needed to reach a clinically valid conclusion to the question of whether newer wavefront-guided technology is comparatively better for correcting HOAs than conventional LASIK in patients with recurrent treatment for hyperopia and hyperopic astigmatism.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, total wavefront-guided ablations have been shown to be safe and effective in the correction of low to moderate levels of HOAs, providing only partial reduction in cases with more extreme aberrations. [30][31][32][46][47][48][49] The wavefront sensors available today analyze up to only 1452 points. 50 Therefore, this type of customized ablation is less effective in patients with high levels of corneal aberrations (eg, previous refractive surgery with older algorithms, surgical complications during LASIK, corneal scars or wounds).…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, software has been developed that calculates ablation profiles to treat different types of HOAs in complicated cases of keratorefractive surgery or in cases in which refractive surgery was performed using older ablation profiles. [30][31][32][33][34][35][36][37] Decentration of the ablation zone during a keratorefractive procedure significantly reduces visual quality after surgery because it can induce a high level of coma-like aberrations. 11,13 In these cases, it is necessary to design an asymmetrical ablation profile to homogenize the corneal surface and obtain good visual performance postoperatively.…”
mentioning
confidence: 99%
“…In addition to good refractive and visual outcomes, WFG enhancements resulted in a reduction of HOAs [41,42] and improvement in low contrast sensitivity and visual symptoms [42]. A comparative study [43] of WFG versus conventional enhancements provided equivalent UCVA and refractive predictability; however, a significant increase in HOAs RMS and decrease in high contrast sensitivity was found in the conventional group that was inversely correlated.…”
Section: Enhancementsmentioning
confidence: 90%
“…Several studies have evaluated the safety and efficacy of WFG enhancements with LASIK or surface ablations to treat residual refractive errors, postoperative HOAs, and refractory LASIK flap striae in symptomatic patients [41][42][43][44][45][46] after previous keratorefractive procedures, as WFG treatments may be most beneficial in patients with highly aberrated corneas. In addition to good refractive and visual outcomes, WFG enhancements resulted in a reduction of HOAs [41,42] and improvement in low contrast sensitivity and visual symptoms [42].…”
Section: Enhancementsmentioning
confidence: 99%